PENGARUH PENGAWASAN PIMPINAN TERHADAP PENINGKATAN PRESTASI KERJA PEGAWAI PADA DINAS PEKERJAAN UMUM KABUPATEN FAKFAK PROVINSI PAPUA BARAT - MOHAN, SIMSON; Mandey, Jantje; Kiyai, Burhanuddin (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract: This study was conducted based on the results prasurvei that civil servants in performing basictasks and functions indicated yet to reach optimum performance. This is presumably related to theimplementation of policy leadership. Thus, the study aims to "Assessing the impact of policy leadership onwork performance of employees at the Department of Public Works Fak-fak West Papua province. Thisresearch applies descriptive method with quantitative approach. Purposive sample of respondents assignedas many as 73 employees, and data collection techniques distributed questionnaires to obtain primary data,secondary data obtained using the documentation techniques. All data and information obtained throughsurveys and direct observation techniques. After the data is collected, then analyzed by using percentageanalysis (frequency table), followed by product moment correlation analysis and simple linear regression.The results showed that: Mean supervisory leadership and job performance of employees at the Departmentof Public Works Fak-fak, according to the results of research are in the category of "medium" or medium.Supervision leadership has positive and highly significant or significant effect on work performance ofemployees at the Department of Public Works Fak-fak West Papua province. Thus, it can be concluded thatthe supervisory leadership with employee work performance related contributory. If the leadership is moreflexible supervision, it will improve the work performance of employees, particularly at the Department ofPublic Works Fak-fak West Papua Province. To improve the work performance of employees, it issuggested that the leadership gives authority to employees in taking the initiative and operational decisionsto carry out their tasks so that work performance will increase even more.Keywords : Supervision leadership, employee job performance